Frequency of psoriatic arthritis in patients of psoriasis presenting to Dermatology Department, Mayo Hospital, Lahore - Sultan, Nadia; Chaudhry, Asad Ali; Rehman, Saima; Butt, Ghazala; Aman, Shahbaz; Shaukat, Shehla; Fatima, Mehek; Omer, Saira (Journal of Pakistan Association of Dermatologists, 2020)
Background Psoriasis is chronic inflammatory disease characterized by red, scaly, sharply demarcated, plaques, mostly over extensor surfaces of the skin.1 Disease is variable in duration & periodicity of flares.1 Psoriatic arthritis is an inflammatory arthritis associated with psoriasis.1 Â Objective To determine the frequency of psoriatic arthritis in patients presenting to a tertiary care setting. Â Methods This was a cross sectional study conducted at OPD, Unit-I, KEMU Mayo Hospital, Lahore for a period of six months. Total 140 patients of psoriasis compatible with the inclusion criteria, were enrolled & evaluated for psoriatic arthritis (as per operational definition). Â Results 140 patients, 87 (62%) M & 53 (38%) F, mean age of 40.97Â±14.74 yrs. were enrolled. 65 (46.42%) cases were positive for PsA, 44 (67.69%) M & 21 (32.31%) F, mean age 42.92Â±13.70. Â Â X MultiCopyPaste Time to upgrade, itâ€™s free! Simply click on the top left of the extension and register to get access to 10 shortcuts. Your email will remain secure, but we might get in touch for your feedback! Â X MultiCopyPaste Time to upgrade, itâ€™s free! Simply click on the top left of the extension and register to get access to 10 shortcuts. Your email will remain secure, but we might get in touch for your feedback! Â X MultiCopyPaste Time to upgrade, itâ€™s free! Simply click on the top left of the extension and register to get access to 10 shortcuts. Your email will remain secure, but we might get in touch for your feedback!